An unconventional hydrogen effect that suppresses thermal formation of the hcp phase in fcc steels. Issue 1 (December 2018) - Koyama, Motomichi; Hirata, Kenji; Abe, Yuji; Mitsuda, Akihiro; Iikubo, Satoshi; Tsuzaki, Kaneaki
Abstract Iron and steels are extensively used as structural materials, and have three primary phase structures: Body-centered cubic (bcc), face-centered cubic (fcc), and hexagonal closed-packed (hcp). Controlling phase stabilities, especially by the use of interstitials, is a universal method that provides a diverse variety of functional and mechanical properties in steels. In this context, hydrogen, which can act as an interstitial species in steels, has been recognized to promote phase transformation from fcc to hcp. However, we here report a dramatic effect of interstitial hydrogen that suppresses this hcp phase transformation. More specifically, the fraction of hcp phase that forms during cooling decreases with increasing diffusible hydrogen content. This new finding opens new venues for thermodynamics-based microstructure design and for development of robust, strong, and ductile steels in hydrogen-related infrastructures.